Balancing Economic Growth and Environmental Sustainability in OilRich Countries (Genius Repository, 2023)
Increasing the GDP of those countries associated with excessive use of energy and materials results in the development of an unsustainable environment. The study will address the potential problems of achieving sustainability in these countries. Through the research of various literature reviews, case studies, and data on this topic, an argument will be made about the development of environmental sustainability in those countries while sustaining economic growth. This study investigates the challenges associated with achieving sustainable development in these countries. Even though the extraction of oil can have a favorable impact on the economy, it can also create potential hazards for society and the environment, necessitating appropriate oversight to guarantee enduring sustainability. By examining applicable literature and case studies, this piece evaluates different methods that nations with significant oil resources can adopt to strike a harmonious equilibrium between their economic expansion and their goals for sustainable development. To conclude, the paper argues that, in addition to economic progress, achieving sustainable development in oil-rich nations necessitates a collaborative and comprehensive approach that prioritizes environmental and social responsibilities. The purpose of this research is to identify the problems connected with long-term development in oil-rich countries. Several aspects that can operate as a backdrop for the respected country were recognized during a conversation on environmental sustainability and economic progress. The majority of Middle Eastern countries are among the most oil-rich in the world. As a result, the countries in the Middle East are the topic of this thesis paper. Because the concept of sustainability implementation has recently become fashionable, the data for this thesis paper was gathered during the last 30 years